Association of Retinal Thickness at Month 1 Postrandomization With Later Thickness and Visual Acuity in Central Vein Occlusion - Scott, Ingrid U.; Oden, Neal L.; Ip, Michael S.; VanVeldhuisen, Paul C.; Blodi, Barbara A. (American journal of ophthalmology, 2024)
To investigate the association of retinal thickness 1 month after the first study aflibercept or bevacizumab injection with later retinal thickness, visual acuity, and number of treatments in eyes enrolled in the Study of COmparative Treatments for REtinal Vein Occlusion 2. Cohort study using data from a randomized clinical trial. Analysis included one eye from each of 350 participants through 2 years of follow-up. Main outcome measures were central subfield thickness (CST), best-corrected visual acuity letter score (VALS), and number of treatments for macular edema. Retinas were classified as thin (≤216 µm), medium (>216 and ≤300 µm), or thick (>300 µm) based on CST. At Month 1, 15% (51/350) of retinas were thin, 57% (199/350) were medium, and 29% (100/350) were thick. Of retinas that were thin at Month 1, 89% to 96% were thin during Months 2 to 12. Over all visits studied, the VALS of eyes with medium retinas at Month 1 was significantly greater than that of eyes with Month 1 thin retinas. During Months 6 to 12 (P < .001) and 12 to 24 (P < .001), the mean number of treatments was highest in eyes with thick retinas and lowest in eyes with thin retinas. Thin retinas had significantly more paracentral acute middle maculopathy and were more likely to have disorganization of the retinal inner layers inside the central subfield, and a history of anti-vascular endothelial growth factor treatment. Having a post-treatment thin retina can be as detrimental to visual acuity as a post-treatment thick retina.